Design and control implementation of fabric-based muscles for a soft wearable exoskeleton - Teo, Tizane Wan Ting (2017)
Artificial muscles that can be used in mechanical devices are created to replace human muscles. They work like an actuator but is much smaller, portable and efficient. Nylon muscles had been discovered in 2014 where it is constructed from silver coated nylon sewing threads which makes it conductive. When the nylon is coiled, and heat-treated, it becomes a muscle that responds to changes in temperature by changing its shape. These muscles acts as an actuator and had been shown to exhibit great potential. A portable, lightweight actuation unit allow users to return to their daily activities faster than conventional means. This can be done by replacing the conventional actuation unit with the nylon muscles, this project aims to produce a light, efficient and reliable actuation unit to be used for soft wearable exoskeleton for rehabilitation and assistive tasks. Models had also been developed to investigate characteristics of the muscles. Results shown that Nylon Muscles produces force when heated, in water and current environment.